(De)securitisation as Philippine responses to the South China Sea disputes - Yacub, Chester (2024)
Over the last three decades, the Philippines has grappled with challenges to its sovereignty, security, and prosperity in response to China’s claims in the South China Sea (SCS) based on historical rights. This thesis explores the Philippines’ strategy for managing what it perceives as persistent threats from China’s maritime assertions. Notably, mainstream IR theories (un)consciously overlook the dynamic interplay between international and internal politics shaping Philippine strategy. In response, the research adopts the Copenhagen School’s Securitization Theory, offering an alternative social constructivist approach to understanding global affairs.